Initial Glottalization and Final Devoicing in Polish English - Schwartz, Geoffrey (Research in Language, 2012)
This paper presents an acoustic study of the speech of Polish leaners of English. The experiment was concerned with English sequences of the type George often, in which a word-final voiced obstruent was followed by a word-initial vowel. Acoustic measurements indicated the degree to which learners transferred Polish-style glottalization on word-initial vowels into their L2 speech. Temporal parameters associated with the production of final voiced obstruents in English were also measured. The results suggest that initial glottalization may be a contributing factor to final devoicing errors. Adopting English-style ‘liaison’ in which the final obstruent is syllabified as an onset to the initial vowel is argued to be a useful goal for English pronunciation syllabi. The implications of the experiment for phonological theory are also discussed. A hierarchical view of syllabic structures proposed in the Onset Prominence environment allows for the non-arbitrary representation of word boundaries in both Polish and English.